Dr. Ernesto Galarza Scholarship Symposium Program 2016 - Chicano/Latino Faculty and Staff Association::::::::::::::: (2024)
Program for the 31st Annual Dr. Ernesto Galarza Scholarship Symposium, held at San Jose State University on Monday, September 19, 2016 in the Dr. Martin Luther King, Jr. Library Cultural Heritage Center. The event included a Registration/Welcome Reception, Welcome by Kathryn Blackmer Reyes (President, CLFSA) and Mauricio Toussaint (Cónsul General de México, San Jose), Introductions by Dr. Julia Curry (Scholarship Coordinator), Keynote Presentation by Alan Gómez (Dr. Ernesto Galarza and IME Scholar), Introduction of Scholarship Recipients by the 2016 Dr. Ernesto Galarza Scholarship Committee (Dr. Joshua Troncoso – Chair, Alicia Casas, Ismael Rey Lara, Francisco Villegas), and Closing Remarks by Dr. Julia Curry. Awards presented included: Dr. Emesto Galarza Scholarship, SJSU President's Scholarship, CLFSA Scholarship, and Galarza Institute Scholarship.